The efficacy of cognitive stimulation, cognitive training, and cognitive rehabilitation for people living with dementia: a systematic review and meta-analysis - Alice Paggetti; Ylenia Druda; Francesco Sciancalepore; Francesco Della Gatta; Antonio Ancidoni; Nicoletta Locuratolo; Paola Piscopo; Luca Vignatelli; Luciano Sagliocca; Antonio Guaita; Piero Secreto; Andrea Stracciari; et al. (GeroScience, 2024)
Cognition-oriented treatments (COTs) are a group of non-pharmacological treatments aimed at maintaining or improving cognitive functioning. Specific recommendations on the use of these interventions in people living with dementia (PLwD) are included in the Italian Guideline on the Diagnosis and Treatment of Dementia and Mild Cognitive Impairment, developed by the Italian National Institute of Health. This systematic review and meta-analysis, based on the GRADE methodology, is part of the guideline. Considered outcomes included the cognitive functions, quality of life, and functional abilities of PLwD, taking into account disease severity, modality and system of delivery, and form of the intervention. The effectiveness of these interventions on caregivers’ outcomes was also assessed. Both group and individual cognitive stimulation were reported as effective in supporting cognitive functions in PLwD at any degree of severity. Individual cognitive training and group cognitive training were reported as effective in improving global cognitive functions in people with mild dementia. Cognitive rehabilitation appeared to be effective only in improving the functional abilities of people with mild dementia. Cognitive rehabilitation appeared to be the most effective in improving caregivers’ outcomes, with results suggesting a reduction in care burden. The observed differences in the effectiveness of these interventions in people with different disease severity can be explained by the intrinsic characteristics of each intervention. Despite the large number of available studies, a high clinical, statistical, and methodological heterogeneity was observed. More methodologically rigorous studies are needed to clarify the effectiveness of each protocol and modality of intervention.

Anthropic vs. natural shoreline changes along the northern Campania coast, Italy - C. Donadio; M. Vigliotti; R. Valente; C. Stanislao; R. Ivaldi; D. Ruberti (Journal of Coastal Conservation, 2018)

Kinematic networks - F. A. Mussa Ivaldi; P. Morasso; R. Zaccaria (Biological Cybernetics, 1988)